Implikasi Yuridis Riwayat tentang Kesalahan Penulisan dalam Mushaf Usmani - Rajafi, Ahmad (Fakultas Syariah IAIN Purwokerto, 2017)
The history of writing error in the Qur'an derived from Aisha and justified by Khalifa Uthman bin Affan received a different responses among Islamic researchers, both from the strictly rejecting that history of writing (riwayat) until to those who accepted the existence the riwayat but with different